Diabetes v nosečnosti - Lakatoš, Josip (Obzornik zdravstvene nege, 1979)
The author gives an epidemiological and pathogenetical historical survey of diabetes in general and adds some present views of the onset of this disease during pregnancy. Glucose tolerance test is the mainstay of diagnosis. Diabetes is classified in groups according to causes and degree of the organism involvement. Guidelines of antenatal care with respect to the coincidence of pregnancy and preexisting disease are given and a special occurrence in pregnancy, the so-called gestation diabetes is described. The paper stresses intensive antenatal care, prevention and management of the foetal involvement.